The Effects of the Addition of Strontium on the Biological Response to Calcium Phosphate Biomaterials: A Systematic Review - Alves Côrtes, Juliana; Dornelas, Jessica; Duarte, Fabiola; Messora, Michel Reis; Mourão, Carlos Fernando; Alves, Gutemberg (Applied sciences, 2024)
Strontium is known for enhancing bone metabolism, osteoblast proliferation, and tissue regeneration. This systematic review aimed to investigate the biological effects of strontium-doped calcium phosphate biomaterials for bone therapy. A literature search up to May 2024 across Web of Science, PubMed, and Scopus retrieved 759 entries, with 42 articles meeting the selection criteria. The studies provided data on material types, strontium incorporation and release, and in vivo and in vitro evidence. Strontium-doped calcium phosphate biomaterials were produced via chemical synthesis and deposited on various substrates, with characterization techniques confirming successful strontium incorporation. Appropriate concentrations of strontium were non-cytotoxic, stimulating cell proliferation, adhesion, and osteogenic factor production through key signaling pathways like Wnt/β-catenin, BMP-2, Runx2, and ERK. In vivo studies identified novel bone formation, angiogenesis, and inhibition of bone resorption. These findings support the safety and efficacy of strontium-doped calcium phosphates, although the optimal strontium concentration for desired effects is still undetermined. Future research should focus on optimizing strontium release kinetics and elucidating molecular mechanisms to enhance clinical applications of these biomaterials in bone tissue engineering.